2017
DOI: 10.1186/s13054-017-1631-3
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variants in SERPINA4 and SERPINA5, but not BCL2 and SIK3 are associated with acute kidney injury in critically ill patients with septic shock

Abstract: BackgroundAcute kidney injury (AKI) is a multifactorial syndrome, but knowledge about its pathophysiology and possible genetic background is limited. Recently the first hypothesis-free genetic association studies have been published to explore individual susceptibility to AKI. We aimed to replicate the previously identified associations between five candidate single nucleotide polymorphisms (SNP) in apoptosis-related genes BCL2, SERPINA4, SERPINA5, and SIK3 and the development of AKI, using a prospective cohor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 34 publications
0
17
0
Order By: Relevance
“…Following up on cumulative findings in urine and serum samples in the identical study population, we selected the genes SERPINA5 and UMOD for genetic analysis. Several SNPs were identified in the past for both genes [25][26][27][28][29][30]. In addition, we aimed to replicate previous studies associating SNPs of COL1A1 and MMP1 genes to SUI [9,31].…”
Section: Discussionmentioning
confidence: 84%
“…Following up on cumulative findings in urine and serum samples in the identical study population, we selected the genes SERPINA5 and UMOD for genetic analysis. Several SNPs were identified in the past for both genes [25][26][27][28][29][30]. In addition, we aimed to replicate previous studies associating SNPs of COL1A1 and MMP1 genes to SUI [9,31].…”
Section: Discussionmentioning
confidence: 84%
“…Vilander LM et al found that the SERPINA4 SNP rs2093266 contributes to the development of severe acute kidney injury. 26 PAI-1 belongs to the SERPIN family, which contributes to an increased risk of recurrent miscarriage. 21 Tamar Madar et al found that low levels of circulating alpha-1 antitrypsin, which belongs to the SERPIN family, are associated with spontaneous abortion.…”
Section: Discussionmentioning
confidence: 99%
“…Variations in or nearby genes related to inflammation, circulation, and cell survival have been suggested in candidate polymorphism studies regarding AKI [7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27]. Additionally, the first hypothesis-free studies in AKI genetic predisposition have been published [28,29,30], with some replicated associations [31]. We chose to test polymorphisms in TNFA (rs1800629 [8,19,21,22,23,24,25,26,27]), IL6 (rs1800796 [24,26] and rs1800795 [19,24,26], rs10499563, rs1474347, rs13306435, rs2069842 and rs2069830), CXCL8 (rs4073 [27]), IL10 (rs1800896 [19,21,23,25,26]), NOS3 (rs2070744 [13,24]), NFKB1A (rs1050851 [32]), AGT (rs699 and rs2493133 [24]), VEGFA (rs2010963 and rs3025039 [27]), EPO (rs1617640 [14]), SUFU (rs10748825 [9]), HIF1A (rs11549465 [15]), PNMT (rs876493 [17]), MPO (rs7208693 [16]), COMT (rs4680 [10,11,12]), HSPB1 (rs2868371 [33]), SFTPD (rs2243639 and rs721917 [34]), HAMP (rs10421768 [35]) and BBS9 (rs10262995 [30]) genes (see d...…”
Section: Methodsmentioning
confidence: 99%
“…In the tertiary analysis we included patients with chronic kidney disease and compared patients with KDIGO stage 2 or 3 AKI to patients without AKI in an adjusted analysis. We used similar covariates to our previously published article [31] (liver failure, body mass index (BMI), use of nonsteroidal anti-inflammatory drugs (NSAID) or warfarin as permanent medication, use of contrast dye prior to ICU admission, use of colloids prior to ICU admission, use of albumin prior to ICU admission, minimum platelet count, and simplified acute physiology score (SAPS) II without renal and age points), omitting the infection focus for irrelevant information, and maximum leucocyte count and operative admission to avoid multicollinearity, while including cardiac surgery status as well as sepsis status. The missing data within covariates (altogether 2.4%) were addressed by imputing (see ESM for details).…”
Section: Methodsmentioning
confidence: 99%